Effectiveness of NSAIDs and Physiotherapy in Acute Low Back Pain on Pain and Function in Workers of Pakistan Textile Industry - Ghafoor, Imran; Kalsoom, Tahirah; Gohar, Awais; Rasul, Akhtar (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To determine the effective treatment option in acute low back pain in workers of textile industry of Pakistan. Methodology: A descriptive cross sectional study from March 208 to August 2018 was conducted at social security hospital Islamabad. Sixty (60) patients with acute low back pain were recruited in the study. They were divided into two groups of thirty (30) each. All the patients filled self-reported questionnaire which includes Oswestry Disability index (ODI), and Visual Analogue scale (VAS). All the outcome measures were taken at baseline and 2 weeks follow up. Results: The mean age of NSAIDs group was 32±7.72 and mean age of NSAIDs & Physio group was 33±9.93 years. The baseline ODI was 13.50 ±7.29, and after two weeks for ODI were 9.63 ±7.33.The NSAIDs and Physio group showed statistically significant for the ODI after two weeks (p<0.05) and VAS after two weeks treatment follow up (p<0.05). Conclusion: It was concluded that NSAIDs along with physiotherapy is more effective then NSAIDs alone. The LBP was significantly associated with smoking, sleep disturbance, education (Primary), work shift (day shift) and type of labor (unskilled).